Immune predisposition drives susceptibility to pneumococcal pneumonia after mild influenza A virus infection in mice - Palani, Sunil; Uddin, Md Bashir; McKelvey, Michael; Shao, Shengjun; Sun, Keer (Frontiers in Immunology, 2023)
A frequent sequela of influenza A virus (IAV) infection is secondary bacterial pneumonia. Therefore, it is clinically important to understand the genetic predisposition to IAV and bacterial coinfection. Here we show that the pathogenicity of IAV/Streptococcus pneumoniae (SPn) coinfection differs between C57BL/6 (B6) and BALB/c mice. Specifically, prior infection with the low-virulent IAV X31 (H3N2) rendered B6 mice extremely susceptible to SPn superinfection, while BALB/c mice remained unaffected.These genetically driven differences were detected regardless of noninvasive or invasive SPn superinfection. Through nonlethal and lethal IAV/SPn coinfection models, we dissected the role of innate and adaptive immune factors in the distinct susceptibilities of BALB/c and B6 mice. We demonstrate that a low dose of X31 infection alone barely induces IFN-γ response in two strains of mice; however, SPn superinfection significantly enhances IFN-γ production in the susceptible B6 mice. As a result, IFN-γ signaling inhibits neutrophil recruitment and bacterial clearance, leading to lethal X31/SPn coinfection in B6 mice. Conversely, neutrophils are competent for bacterial control in coinfected BALB/c mice.Collectively, our results establish that type 1 immune predisposition plays a key role in lethal susceptibility to pneumococcal pneumonia after mild IAV infection.